The impact of Covid-19 pandemic on corporate social responsibility and marketing philosophy - He, Hongwei; Harris, Lloyd (Journal of business research, 2020)
In this article, we offer some initial examination on how Covid-19 pandemic can influence the developments of CSR and marketing. We argue that Covid-19 pandemic offers a great opportunity for businesses to shift towards more genuine and authentic CSR and contribute to address urgent global social and environmental challenges. We also discuss some potential directions of how consumer ethical decision making will be shifted to due to the pandemic. In our discussion of marketing, we outline how we believe marketing is being affected by this pandemic and how we think this will change, not only the context of marketing, but how organizations approach their strategic marketing efforts. We end the paper with a identifying a number of potentially fruitful research themes and directions.